A Phenomenological Study of Teachers' Perceptions on Multiple Leadership Styles Among Secondary School Principals - Safwandi Safwandi; Aan Komariah; Asep Suryana; Eka Prihatin (Universitas Negeri Malang, 2025)
Abstract: This study explores teachers' perceptions of secondary school principal leadership practices in Indonesia, examining how transformational, instructional, distributive, and servant leadership dimensions integrate in daily practice. The research identifies specific leadership behaviors perceived as most significant by teachers and analyzes their impact on teacher well-being, motivation, and professional commitment in Indonesian secondary education contexts. The study employed a descriptive phenomenological design with a qualitative approach. Data were collected through in-depth semi-structured interviews with one experienced secondary school teacher using purposive sampling. Analysis utilized Braun and Clarke's six-phase thematic analysis approach, with ATLAS.ti version 23 software facilitates systematic coding and pattern visualization. Four major themes emerged: (1) Personal Care and Attention, reflecting servant leadership through regular evaluation and crisis support; (2) Authority Delegation and Trust, demonstrating distributive leadership with structured guidance; (3) Teacher Professional Development, through weekly dissemination programs and classroom observation; and (4) Transformational Leadership, involving meaningful vision formulation, participation and multichannel communication. However, bidirectional collaborative learning between principals and teachers showed limitations. This study provides the first empirical evidence of multi-dimensional leadership integration in Indonesian secondary school contexts, advancing knowledge by demonstrating how Western leadership theories adapt within non-Western cultural frameworks. It introduces teachers' voices as a primary data source, offering insider perspectives often neglected in leadership studies and revealing authentic distributive leadership implementation challenges within hierarchical cultures. Findings inform principal training program development and educational policy formulation regarding competency standards and performance evaluation systems in Indonesian secondary education. Keywords: educational leadership, transformational leadership, instructional leadership, distributive leadership, servant leadership